2008
DOI: 10.5194/adgeo-16-63-2008
|View full text |Cite
|
Sign up to set email alerts
|

First results on a process-oriented rain area classification technique using Meteosat Second Generation SEVIRI nighttime data

Abstract: Abstract.A new technique for process-oriented rain area classification using Meteosat Second Generation SEVIRI nighttime data is introduced. It is based on a combination of the Advective Convective Technique (ACT) which focuses on precipitation areas connected to convective processes and the Rain Area Delineation Scheme during Nighttime (RADS-N) a new technique for the improved detection of stratiform precipitation areas (e.g. in connection with mid-latitude frontal systems). The ACT which uses positive bright… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The same holds true for low BT 10.8 together with high Δ T WV6.2–IR10.8 values (Figure 3b). This corroborates the findings of Thies et al [2008c; B. Thies et al, submitted manuscript, 2007] that Δ T WV6.2–IR10.8 and Δ T WV7.3–IR12.1 increase with increasing cloud top height. At the same time, the higher the cloud reaches into the atmosphere the lower becomes BT 10.8 .…”
Section: Process Separation and Rainfall Intensity Differentiation Wisupporting
confidence: 89%
See 1 more Smart Citation
“…The same holds true for low BT 10.8 together with high Δ T WV6.2–IR10.8 values (Figure 3b). This corroborates the findings of Thies et al [2008c; B. Thies et al, submitted manuscript, 2007] that Δ T WV6.2–IR10.8 and Δ T WV7.3–IR12.1 increase with increasing cloud top height. At the same time, the higher the cloud reaches into the atmosphere the lower becomes BT 10.8 .…”
Section: Process Separation and Rainfall Intensity Differentiation Wisupporting
confidence: 89%
“…Concerning the two WV and two IR channels of SEVIRI, the studies of Thies et al [2008c; also Detection of high rain clouds using water vapor emission—Transition from Meteosat First (MVIRI) to Second Generation (SEVIRI), submitted to Advanced Space Research , 2007] revealed that the four possible WV‐IR combinations show different sensitivities to the cloud top height at different levels, which provide useful information for the detection and classification of convectively dominated precipitation areas. To incorporate the different sensitivities on cloud top height into the detection scheme, the two channel differences Δ T WV6.2–IR10.8 and Δ T WV7.3–IR12.1 have been chosen.…”
Section: Process Separation and Rainfall Intensity Differentiation Wimentioning
confidence: 99%
“…As these microphysical properties can be derived from band combinations between the water vapour bands and the middle and thermal infrared bands, the five most important combinations between these bands were included in the model data (cf. Kühnlein et al [31], Thies et al [32]). …”
Section: Preprocessing and Input Featuresmentioning
confidence: 99%
“…The extinction coefficients for water in the atmospheric window band with longer wavelengths are larger than those with shorter wavelengths in all the solid, liquid, and gaseous states. Therefore, the cloud water path (CWP) can be described as the BT differences of two atmospheric window bands, called IR split-window (SW) technique (Inoue et al 1985;Lensky and Rosenfeld 2003;Thies et al 2008a). The original Himawari-8 standard data were provided by the Japan Meteorological Agency (JMA).…”
Section: Datamentioning
confidence: 99%